Frequency of Type of Hearing Loss in Patients Presenting to ENT Outpatient Clinics - Aria Masoom, Abdul Manan Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hearing loss is a major health disorder that negatively affect the life of an individual. It has various type and many causes. Objective: The aim of this study was to find out the Frequency of Type of Hearing Loss in Patients Presenting to ENT Outpatient Clinics Material and method: This prospective study was conducted at the Department of ENT, Bolan Medical College / Complex Hospital, Quetta from July 2022 to December 2022 after taking approval from the research committee of the institute. A total of 410 individuals of both genders and different age groups (5years or above) presented sudden sensorineural hearing loss in one or both ears were included. Otoscopy was performed to check for any disease in the middle ear, tympanic membrane, and ear canal. To evaluate the degree of clinical hearing, tests using conversational and whispered voices were conducted. The rest of the neck and ENT were thoroughly inspected. For every patient, pure tone audiograms (PTA) were acquired. Where applicable, impedance audiography was used. Analyses were done on the basis of PTA hearing impairment. All the data was recorded on specific proforma and analyzed through SPSS version 16. Results: A total of 410 individuals were examined in the study out of which 59% were male and 41% were female .The mean age of the study population was 30 (ranged 15-85) years. Hearing loss was most prevalent in the 5-10 years age group 27.5%. The most common type of hearing impairment was Conductive deafness 48.7% followed by Sensorineural loss 39.0% and Mixed 1.2%.Among the etiologies the most prevalent reason of hearing loss was Chronic suppurative otitis media 46.3% followed by presbyacusis 17.5%, NIHL 14.1%, and OME 12.6%. The most prevalent condition causing conductive & mixed hearing loss was chronic suppurative otitis media, while the most common condition causing sensorineural loss was presbyacusis. Conductive loss was most prevalent in the younger age group whereas sonsorineural loss was more prevalent in the elder age group. Conclusion: The current study concluded that according to pure tone audiography, conductive hearing loss is the most common kind of hearing loss among individuals who attend ENT clinics, and it mostly affects children. The most frequent causes are otitis media with effusion and chronic suppurative otitis media. Keywords: Frequency; Hearing Loss; Ear; Nose; Throat